IMPROVING ENGLISH GRAMMAR COMPETENCE THROUGH THE TASK-BASED LANGUAGE TEACHING: CLASSROOM ACTION RESEARCH AT MAN 1 PROBOLINGGO - Yusrina, Emilia; Tirmidi, Tirmidi; Fauz, Ahmad (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improve students’ grammar skills the Task-Based Language Teaching Approach for Grade XI Students at MAN 1 PROBOLINGGO. This research employed a Classroom Action Research (CAR) with 8 eleventh-grade students. Data were collected through grammar tests administered before and after the intervention, supported by classroom documentation. The findings indicate a substantial increase in students’ grammar performance after the treatment. The mean pretest score was 28,75, which rose to 46.25 on the posttest. The average improvement of 17.50 points demonstrates the positive effect of the instructional intervention. Therefore, Task-Based Language Teaching is proven to be an effective approach to improve students’ grammar achievement and interest in English learning.